2005
DOI: 10.1021/bi048657a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Crystallographic Analysis of Active Site Mutants of Escherichia coli γ-Aminobutyrate Aminotransferase

Abstract: The E. coli isozyme of gamma-aminobutyrate aminotransferase (GABA-AT) is a tetrameric pyridoxal phosphate-dependent enzyme that catalyzes transamination between primary amines and alpha-keto acids. The roles of the active site residues V241, E211, and I50 in the GABA-AT mechanism have been probed by site-directed mutagenesis. The beta-branched side chain of V241 facilitates formation of external aldimine intermediates with primary amine substrates, while E211 provides charge compensation of R398 selectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…The HAB aminotransferase described here showed 66% amino acid sequence identity with the annotated 4-aminobutryate aminotransferase from Pseudomonas syringae ( Table 1). The protein identified here also showed 46% amino acid sequence identity to the E. coli 4-aminobutyrate aminotransferase for which an X-ray structure is known (17).…”
Section: Discussionmentioning
confidence: 63%
“…The HAB aminotransferase described here showed 66% amino acid sequence identity with the annotated 4-aminobutryate aminotransferase from Pseudomonas syringae ( Table 1). The protein identified here also showed 46% amino acid sequence identity to the E. coli 4-aminobutyrate aminotransferase for which an X-ray structure is known (17).…”
Section: Discussionmentioning
confidence: 63%
“…This model fits well with the abundant evidence, demonstrating that, in vivo, Orn-AT operates in the direction in which ornithine and ketoglutarate are the substrates (4). Moreover, the hypothesis is supported by the recently published structure (20) of a mutant form of GABA-AT (I50Q) that is partially in the E M form and in which the homologue of Glu-235 (E211) is seen to be rotated away from the homologous conserved arginine. Furthermore, the structure of the homologue of Orn-AT-E235S (GABA-AT-E211S), in which the switch must be permanently open, shows the enzyme to be entirely in the E M form (20), reinforcing the proposal that the status of the cofactor and the Glu-235 switch are linked.…”
Section: Properties Of Mutant Forms Of Orn-at-mentioning
confidence: 87%
“…The identity and similarity of the amino acid sequences of PuuE and GabT were 54.2% and 67.4%, respectively. The sequence alignment between PuuE and GabT (data not shown) suggested that Lys-267 of PuuE (corresponding to Lys-268 in GabT, which is an important residue for GabT activity [10]) is an important residue for the activity. Site-directed mutagenesis of PuuE(K267A) was performed to confirm that Lys-267 is an important residue of PuuE.…”
Section: Fig 2 (A)mentioning
confidence: 99%